Basic Psychological Needs Satisfaction and Student Engagement: The Importance of Novelty Satisfaction - Benlahcene, Abderrahim; Kaur, Amrita; Awang Hashim, Rosna (Emerald Publishing Limited, 2021)
Purpose – The purpose of this paper is to examine the associations between students’ basic psychological needs satisfaction, including novelty satisfaction, and the four aspects of student engagement. Design/methodology/approach – Data were collected from a total sample of 743 undergraduate students from three public universities in northern Malaysia. Structural equation modelling (SEM) was used to analyse the data. Findings – Competence and relatedness were positively related to the four aspects of student engagement, while autonomy satisfaction was found to relate to agentic engagement. Novelty satisfaction, on the other hand, is related positively with behavioural, emotional and cognitive engagement. Research limitations/implications – The results provide a new understanding on the importance of novelty satisfaction alongside existing needs in self-determination theory (SDT) in enhancing student engagement. Practical implications – Educators are encouraged to develop strategies to provide novelty support and facilitate students’ basic needs satisfaction in order to establish a motivational learning environment that vitalises students’ engagement. Originality/value – This study breaks new ground by testing the unique relationships of novelty satisfaction along with the psychological needs for autonomy, competence and relatedness, with the four aspects of student engagement in higher education.